Mental State of the Workers of the Ministry of Higher Education and Scientific Research (MESRS) in Benin in 2018 - GANSOU, Magloire; Eganhoui, Denis; KLIKPO, ELVYRE; HOUESSOU, PATRICK YÉLINDO DOSSOU (My University, 2019)
The work environment is an environment at risk for the psychological well-being of workers. This research is conducted on a population of 348 workers from the Ministry of Higher Education and Scientific Research (MESRS) in Benin. It was a cross, descriptive study, with an analytical goal, with non-probabilistic sampling, and by convenience. The research tools were documentation, SATIN scales, interview and observation. The results processed and analyzed by the Excel software, and R show that the general health is poor in 14.7% of workers, average in 27.9%, and good in 57.5%. Psychological health is poor in 10.3%, average in 18.1%, and good in 71.6%. Physical health is poor in 6.1% of workers, average in 24.4%, and good in 69.6%. Similarly, stress is bad for 13.5% of workers, average for 37.7%, and good for 48.8%. Psychosomatic symptoms are poor in 19.6% of workers, average in 21.1% and 59.2%. The symptoms are poor in 31.0% of workers, average in 16.5%, and good in 52.5%. The well-being of this population is attributable to several factors, the predominant element of which is the organizational environment and its conditions. Better consideration of the factors that strengthen human capital is essential for the physical and psychological well-being of MESRS worker
Keywords: Mental State; MESRS Workers; Psychological Distress; Benin